First study of host-plant preferences of Sinopla perpunctatus (Hemiptera: Acanthosomatidae), a stink bug from the Andean-Patagonic forest - Pietrantuono, Ana Laura (2014)
Host plants of phytophagous insects are not equally attractive. The aim of this study was to evaluate the host-plant behavior of Sinopla perpunctatus Signoret (Hemiptera: Acanthosomatidae) and determine which parameters influence the insect’s motivation. Sinopla perpunctatus is a green stink bug present in the Andean-Patagonian forest associated with various host species of Nothofagus (Fagales: Nothafagaceae) southern beech trees. For the assays, we collected adults at Quilanlahue forest (Neuquen, Argentina), an area affected by the deposition of volcanic ash, whose effects we decided to evaluate. A sequence of paired comparisons was used to evaluate the host-plant preferences. Branches from N. antarctica, N. nervosa, N. obliqua and plastic leaves (control), with or without ash were the stimuli offered. In total we performed 18 combinations of paired tests to evaluate the different combinations of treatments. We considered the choices of each individual by day as the response variable. The data were analyzed by several models that explain the probability of an individual choosing a particular option depending on host plant preferences and the effect of different parameters of motivation (including the age, ash, home effect and combinations).Thus a total of eight models were proposed to explain the data, from which we selected the model with the lowest value of the deviance information criterion (DIC). The selected model established that preferences were determined by the motivation for change after the organism has already made a choice (i.e., home effect). The preferred host plants of S. perpunctatus were found to be N. antarctica and N. obliqua, while its preference for N. nervosa occupied a second place. Physical or chemical defenses of the leaves among species could explain this rank. However, volcanic ash was found to have no effect on motivation or host preference. Finally, we concluded that such studies of behavior and of parameters that may affect insect motivation should allow us to reach greater understandings of insect-plant interactions.